A systematic review of decision aids for patients making a decision about treatment for early breast cancer. (April 2016) - Nicholas Zdenkowski,; Butow, Phyllis; Tesson, Stephanie; Boyle, Frances
Abstract: Several complex treatment decisions may be offered to women with early stage breast cancer, about a range of treatments from different modalities including surgery, radiotherapy, and endocrine and chemotherapy. Decision aids can facilitate shared decision-making and improve decision-related outcomes. We aimed to systematically identify, describe and appraise the literature on treatment decision aids for women with early breast cancer, synthesise the data and identify breast cancer decisions that lack a decision aid. A prospectively developed search strategy was applied to MEDLINE, the Cochrane databases, EMBASE, PsycINFO, Web of Science and abstract databases from major conferences. Data were extracted into a pre-piloted form. Quality and risk of bias were measured using Qualsyst criteria. Results were synthesised into narrative format. Thirty-three eligible articles were identified, evaluating 23 individual treatment decision aids, comprising 13 randomised controlled trial reports, seven non-randomised comparative studies, eight single-arm pre-post studies and five cross-sectional studies. The decisions addressed by these decision aids were: breast conserving surgery versus mastectomy (+/− reconstruction); use of chemotherapy and/or endocrine therapy; radiotherapy; and fertility preservation. Outcome measures were heterogeneous, precluding meta-analysis. Decisional conflict decreased, and knowledge and satisfaction increased, without any change in anxiety or depression, in most studies. No studies were identified that evaluated decision aids for neoadjuvant systemic therapy, or contralateral prophylactic mastectomy. Decision aids are available and improved decision-related outcomes for many breast cancer treatment decisions including surgery, radiotherapy, and endocrine and chemotherapy. Decision aids for neoadjuvant systemic therapy and contralateral prophylactic mastectomy could not be found, and may be warranted. Highlights: Thirty-three studies were identified, evaluating 23 individual decision aids (DAs). DAs: were acceptable, improved knowledge, decreased decisional conflict. No single format (internet, booklet, audio, video) was clearly superior to others. DAs for surgical, systemic therapy, radiotherapy and fertility options were found. DAs for neoadjuvant systemic therapy and prophylactic mastectomy may be warranted.